BATAKO GREEN MATERIAL - I Gede Yohan Kafrain; Hence Roring; Fenny Moniaga (Rang Teknik Journal, 2024)
In recent years, there has been a lot of development of wall materials derived from waste, such as husk ash waste, plastic bottle waste, plastic ore waste and fly ash waste. The aim of this research is to make bricks from plastic waste and fly ash waste but not using cement as a binder but using an alkali activator. By not using cement and using fly ash waste and plastic waste, this will reduce environmental pollution both due to cement production and plastic waste which has become a global problem. In this research, bricks were made by mixing plastic, fly ash and alkali activator as a binding agent. The mixture variations used are the ratio of plastic and fly ash with plastic content of 50%, 30% and 20%. In this research, the compressive strength of green material brick concrete was found to be 49.46 kg/cm2, 106.35 kg/cm2, and 125.29 kg/cm2 respectively. The weight of the green material bricks is 1.326 kg/cm3, 1.482 kg/cm3 and 1.502 kg/cm3. The water absorption of green material bricks is 8.29%, 6.49% and 5.36%. Based on SNI 03-0349-1989 green material bricks with a plastic content of 50% are included in quality III solid bricks, while those with plastic content of 30% and 20% are included in quality I solid bricksKeywords: Brick, Plastic, Fly Ash, Green Material